ANALISIS KINERJA DINAS MATERIEL DAN SENJATA TNI ANGKATAN LAUT MELALUI PENDEKATAN BUDAYA ORGANISASI DAN KOMPETENSI YANG DIMODERASI AUTOMATIC ADJUSTMENT - Hermawan, Aries; Suharjo, Bambang; Kristiyono, Kristiyono (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
The Indonesian Navy's weapons and electronics materials service has a very strategic function in the Indonesian Navy. one of its functions is to carry out planning and continuous evaluation of activities in the field of electronics and weapons including ammunition material, navigation, electronic instruments, drones, simulators, sensors, controls and weapons, sensors, controls and weapons. The type of research used in this research is qualitative. The location of this research is the Indonesian Navy's weapons and electronics materials service, Subdiharsewaco Disharkap Koarmada I, Subdiharsewaco Disharkap Koarmada II, Subdiharsewaco Disharkap Koarmada III, Disharsewaco Disharkap Kolinlamil, Subdisren Disharmat Kormar. The analysis tool used is NVIVO 12. The results of the research are that the planning and budget proposed by Dissenlekal are in accordance with Dissenlekal's needs, but with the automatic adjustment, planning cannot reach 100%. The organizational culture of the Indonesian Navy's weapons and electronics materiel service reflects a good, positive, supportive and inclusive work environment. The competency of personnel in this organization is very good, with in-depth knowledge and high skills. The performance of personnel in this organization is very good, with high quality and quantity of work, consistent punctuality, and strong occupational safety awareness and compliance. Organizational culture and competence influence organizational performance. The Indonesian Navy's weapons and electronics materials service has strong adaptability in dealing with budget changes resulting from the automatic adjustment program. The existence of automatic adjustments affects organizational performance but is not significant. With a good organizational culture and competence, good performance will result despite automatic adjustments.